Peran Kepala Madrasah dalam Mengembangkan Budaya Religius melalui Sholat Dhuha Berjamaah di MI Lailatul Qadar Cianjur - Maswiah; Dera Nugraha; Alfa Rohmatin (PT. Nawa Edukasi Nusantara, 2026)
Religious culture in Islamic elementary schools requires consistent leadership, structured habituation, and active participation from all school members. This study aims to describe the role of the madrasah principal in developing the religious culture of congregational Dhuha prayer at MI Lailatul Qadar Cianjur. This research used a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving the madrasah principal, teachers, and students. The data were analyzed through data reduction, data display, and conclusion drawing, while data validity was strengthened through source and technique triangulation. The findings show that the madrasah principal plays a central role as planner, organizer, role model, supervisor, evaluator, and motivator in developing congregational Dhuha prayer as a religious culture. The program is implemented through routine scheduling, teacher assistance, student guidance, supervision, and continuous evaluation. The activity contributes to the formation of discipline, responsibility, religious awareness, orderliness, and togetherness among students. The study concludes that congregational Dhuha prayer can become an effective model of religious habituation when supported by consistent principal leadership, teacher involvement, and a supportive madrasah environment.